The Effect of Emotional Intelligence and Self-Control on Aggressive Behavior and PAI Learning Achievement of Students in State Vocational High School 6 Malang - Dzaki Aflah Zamani; Mohammad Asrori; Mulyono Mulyono (At-Ta'dib, 2022)
The study aimed to know: 1) the effect of emotional intelligence on aggressive behavior, 2) the effect of self-control on aggressive behavior, 3) the influence of emotional intelligence on Islamic education’s learning achievement, 4) the effect of self-control on Islamic education’s learning achievement, 5) the influence of behavior aggressive towards Islamic education’s learning achievement, 6) the influence of emotional intelligence on Islamic education’s learning achievement through aggressive behavior, 7) the effect of self-control on Islamic education’s learning achievement through aggressive behavior. This study used quantitative approach with the correlational method. Data was collected using a questionnaire to measure emotional intelligence, self-control, and aggressive behavior. Meanwhile, the researcher used the documentation of the final score of the report to measure the Islamic education’s learning achievement of students. The sample was 100 respondents. The data analysis technique used the Partial Least Square (PLS) test with smartPLS software. The results showed that: (1) significant negative effect of emotional intelligence on students' aggressive behavior (p-value 0.001 <0.05). (2) significant negative effect of self-control on students' aggressive behavior (p-value 0.000 <0.05). (3) significant positive effect of emotional intelligence on students' learning achievement (p-value 0.030 <0.05). (4) significant positive effect of self-control on students' learning achievement (p-value 0.037 <0.05). (5) significant negative effect of aggressive behavior on students' learning achievement (p-value 0.004 <0.05). (6) significant indirect effect of emotional intelligence on learning achievement through student aggressive behavior (p-value 0.028 <0.05). (7) significant indirect effect of self-control on learning achievement through student aggressive behavior (p-value 0.011 <0.05).